(untitled) - O'Neil, William J. (New York, 2004)
Completely updated and revised with new quotes and charts for the new year, How to Make Money in Stocks Desk Diary 2005 is an indispensable day-at-a-glance resource for the serious investor. Filled with in-depth market insights, How to Make Money in Stocks Desk Diary 2005 helps reinforce, reinvigorate, and review the concepts and principles of the CAN SLIM™ system of investing developed by William J. O’Neil and used by millions of investors. Used in conjunction with the bestselling How to Make Money in Stocks, this desk diary will keep you focused on learning and implementing sound investment techniques that will grow your portfolio in any market.
Keywords: Investments,Stocks